Lo schermo di scrittura - Bernard Stiegler (Rivista di Estetica, 2016)
The article considers the increasing influence acquired displayed by the screens of our devices for communicating information and elaborating data. These screens are becoming “writing screens”. They constitute a danger for our individual and collective experience, since they redesign in depth the temporality and rhythm of all human activities, above all work, which becomes now a life form that never stops accompanying our existence. According to Derrida’s concept of pharmakon, the author argues that the very concept of “writing screen” should be interpreted from within its nature, attempting to elaborate a new “hermeneutics” of screens – a hermeneutics capable of rendering a shared meaning, as well as the possibility of having experience through the new interactive media and devices.